THE INFLUENCE OF CULTURAL BACKGROUND ON ENGLISH LANGUAGE ACQUISITION IN MULTILINGUAL SETTINGS - Husna Imro'athush Sholihah; Fety Surfaifel; Rosdiana Mata (Indonesian Journal of Education (INJOE), 2024)
Today’s generation is filled with globalization, making individuals appreciate the English language, although its process of acquisition may vary due to the sociocultural factors of the learners. The study in this research uses literature. The results showed that the cultural influences and language approach towards learning English as a second language in a multilingual classrooms setting differs with regards to the strategies employed in learning, the degree of anxiety while communicating, attitudes towards English language, internal desire to learn the language and the impact of the native language. So in e-learning multicultural education, the limitation of this study indicates the consistency-oriented principles of cultural awareness should be altered to address the issues raised in this study on how better English language learning can be optimized in multilingual societies.